From "Rational Utopia" to "Will-to-Utopia". On the "Post-modern" Turn in the Recent Work of Agnes Heller - Tormey, Simon (1998)
Agnes Heller recently described her position as 'postmodernist', suggesting a move from a political radical to a politically liberal or 'neoconservative' position. The aim of this paper is to assess the degree to which Heller can still be regarded as a radical political thinker through an evaluation of her work on autonomy, democracy and contingency all of which remain key concepts in her thinking about the political. We find in each case that whilst many of the motifs of her critical Marxist period recur in her recent work, they are losing their oppositional or 'negative' character in the sense that making these motifs operational would require changes to the structure or functioning of liberal-capitalism. Whils remaining in some sense a radical thinker Heller has moved from the advocacy of a 'rational utopia' to a form of theorising which I describe as 'will-to-utopia': radical at the surface yet conservative at the core.